Effect of HIV co-infection on adherence to a 12-week regimen of hepatitis C virus therapy with ledipasvir and sofosbuvir. (January 2016) - Townsend, Kerry; Petersen, Tess; Gordon, Lori A.; Kohli, Anita; Nelson, Amy; Seamon, Cassie; Gross, Chloe; Tang, Lydia; Osinusi, Anu; Polis, Michael A.; Masur, Henry; Kottilil, Shyam
Abstract : Objective: As the treatment of hepatitis C virus (HCV) infection has evolved to directly acting antiviral agents, the impact of these directly acting antiviral-only regimens on improving adherence to HCV treatment in HIV/HCV coinfected populations has not been evaluated. The study compared adherence to ledipasvir/sofosbuvir (LDV/SOF) in HCV monoinfected and HIV/HCV coinfected individuals. Design: Adherence was measured from participants in two phase 2 open-label studies (NCT01805882 and NCT01878799). Methods: HCV treatment-naive, genotype 1 study individuals [HCV monoinfected participants ( N = 20) and HIV/HCV coinfected participants, antiretroviral untreated ( N = 13) or on combination antiretroviral therapy ( N = 37)] were treated with LDV (90 mg) and SOF (400 mg) administered as one tablet once daily for 12 weeks. Adherence was measured using three tools: medication event monitoring system cap, pill count, and patient report. Results: Participants were predominately African American (83%) and male (73%), with a median age of 59 years. Participants had prompt HCV viral load decline and high adherence rates (97 ± 0.5% by medication event monitoring system). Participant adherence decreased significantly from early (baseline week 4) as compared with late (weeks 8–12) in therapy in all three groups – HCV monoinfected ( P = 0.01), HIV/HCV antiretroviral untreated ( P = 0.02), and HIV/HCV antiretroviral treated participants ( P = 0.01). Conclusion: Adherence to LDV/SOF in this urban population was high and comparable between HCV monoinfected and HIV/HCV coinfected participants regardless of antiretroviral use. Abstract : Supplemental Digital Content is available in the text